Treatment of first episode schizophrenia with low-dose haloperidol : a study in the Western Cape Province of South Africa - Oosthuizen, P. P. (Petrus Paulus) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--Stellenbosch University, 2003.